1994
DOI: 10.1164/ajrccm.149.6.8004315
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function abnormalities in thalassemia major and the role of iron overload.

Abstract: To determine the predominant abnormality of pulmonary function in patients with thalassemia major (TM), we evaluated 29 patients with TM who were receiving hypertransfusion therapy and chelation with desferrioxamine (DFO), and who ranged in age from 6 to 40 yr (mean 19.8 +/- 8.5 yr). A reduction in the total lung capacity (TLC) was the most striking abnormality, found in 21 of 29 patients (79%). Fourteen of these patients (67%) had a moderate or severe reduction in TLC. Expiratory flow rates, FEV1, and FEF25-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
77
2
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(102 citation statements)
references
References 10 publications
13
77
2
10
Order By: Relevance
“…Among the thalassemic subjects, restrictive lung function abnormality was the most common (42/63) observation documented in this study. Our findings are consistent with those of Carnelli et al, 1 Factor et al, 2 Tai et al, 5 Luyt et al, 6 and Filosa et al 7 What is unique to our study is that it was performed exclusively in children, while those studies mentioned earlier were all performed in both children and adults, with a considerably older mean age. Therefore, our study shows that lung dysfunction in thalassemic patients has occurred since childhood.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Among the thalassemic subjects, restrictive lung function abnormality was the most common (42/63) observation documented in this study. Our findings are consistent with those of Carnelli et al, 1 Factor et al, 2 Tai et al, 5 Luyt et al, 6 and Filosa et al 7 What is unique to our study is that it was performed exclusively in children, while those studies mentioned earlier were all performed in both children and adults, with a considerably older mean age. Therefore, our study shows that lung dysfunction in thalassemic patients has occurred since childhood.…”
Section: Discussionsupporting
confidence: 93%
“…However, no correlation was found between serum ferritin levels and any of the lung function values. This finding supported those discovered by Tai et al, 5 and Luyt et al 6 , but contrasted with studies by Carnelli et al, 1 Factor et al, 2 and Filosa et al 7 It is suggested that the duration of iron overload may be more important than the actual amount of iron provided through transfusions. 2 Moreover, serum ferritin levels change during the process of chelation, and do not necessarily reflect total body iron stores.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations